Enteroids Generated from Patients with Severe Inflammation in Crohn's Disease Maintain Alterations of Junctional Proteins. (28th April 2020) - Meir, Michael; Salm, Jonas; Fey, Christina; Schweinlin, Matthias; Kollmann, Catherine; Kannapin, Felix; Germer, Christoph-Thomas; Waschke, Jens; Beck, Christopher; Burkard, Natalie; Metzger, Marco; Schlegel, Nicolas
Abstract: Background: The mechanisms underlying loss of intestinal epithelial barrier [IEB] function in Crohn's disease [CD] are poorly understood. We tested whether human enteroids generated from isolated intestinal crypts of CD patients serve as an appropriate in vitro model to analyse changes of IEB proteins observed in patients' specimens. Methods: Gut samples from CD patients and healthy individuals who underwent surgery were collected. Enteroids were generated from intestinal crypts and analyses of junctional proteins in comparison to full wall samples were performed. Results: Histopathology confirmed the presence of CD and the extent of inflammation in intestinal full wall sections. As revealed by immunostaining and Western blot analysis, profound changes in expression patterns of tight junction, adherens junction and desmosomal proteins were observed in full wall specimens when CD was present. Unexpectedly, when enteroids were generated from specimens of CD patients with severe inflammation, alterations of most tight junction proteins and the majority of changes in desmosomal proteins but not E-cadherin were maintained under culture conditions. Importantly, these changes were maintained without any additional stimulation of cytokines. Interestingly, qRT-PCR demonstrated that mRNA levels of junctional proteins were not different when enteroids from CD patients were compared to enteroids from healthy controls. Conclusions: These data indicate that enteroids generated from patients with severe inflammation in CD maintain some characteristics of intestinal barrier protein changes on a post-transcriptional level. The enteroid in vitro model represents an appropriate tool to gain further cellular and molecular insights into the pathogenesis of barrier dysfunction in CD.